A structural and computational comparison of close contacts and related intermolecular energies of interaction in the structures of 1, 3‐diiodo‐5‐nitrobenzene, 1, 3‐dibromo‐5‐nitrobenzene, and 1, 3‐dichloro‐5‐nitrobenzene. Issue 10 (23rd September 2022) - Bosch, Eric; Bowling, Nathan P.; Speetzen, Erin D.
Abstract : The relationship between close intermolecular contacts and intermolecular energies of interaction within the crystals of the 1, 3‐dihalo‐5‐nitrobenzenes with Cl, Br, and I is probed. The results reveal the relative role of π‐stacking, self‐complementary halogen…O(nitro) bonds, bifurcated C—H…O(nitro) interactions and Type I halogen–halogen interactions in terms of cohesive intermolecular energies of interaction. Abstract : 1, 3‐Diiodo‐5‐nitrobenzene, C6 H3 I2 NO2, and 1, 3‐dibromo‐5‐nitrobenzene, C6 H3 Br2 NO2, crystallize in the centrosymmetric space group P 21 / m, and are isostructural with 1, 3‐dichloro‐5‐nitrobenzene, C6 H3 Cl2 NO2, that has been redetermined at 100 K for consistency. While the three‐dimensional packing in all three structures is similar, the size of the halogen atom affects the nonbonded close contacts observed between molecules. Thus, the structure of 1, 3‐diiodo‐5‐nitrobenzene features a close Type 1 I…I contact, the structure of 1, 3‐dibromo‐5‐nitrobenzene features a self‐complementary nitro‐O…Br close contact, while the structure of 1, 3‐dichloro‐5‐nitrobenzene also has a self‐complementary nitro‐O…Cl interaction, as well as a bifurcated C—H…O(nitro) close contact. Notably, the major energetically attractive intermolecular interaction between adjacent molecules in each of the three structures corresponds to a π‐stacked interaction. The self‐complementary halogen…O(nitro) and C—H…O(nitro) interactions correspond to significant cohesive attraction between molecules in each structure, while the Type 1 halogen–halogen contact is weakly cohesive.